Crystal structure of the apo form of a β‐transaminase from Mesorhizobium sp. strain LUK - Kwon, Sunghark (Protein Sci, 2019)
Pyridoxal 5′‐phosphate (PLP)‐dependent β‐transaminases (βTAs) reversibly catalyze transamination reactions by recognizing amino groups linked to the β‐carbon atoms of their substrates. Although several βTA structures have been determined as holo forms containing PLP, little is known about the effect of PLP on the conversion of the apo structure to the holo structure. We determined the crystal structure of the apo form of a βTA from Mesorhizobium sp. strain LUK at 2.2 Å resolution to elucidate how PLP affects the βTA structure. The structure revealed three major disordered regions near the active site. Structural comparison with the holo form also showed that the disordered regions in the apo form are ordered and partially adopt secondary structures in the holo form. These findings suggest that PLP incorporation into the active site contributes to the structural stability of the active site architecture, thereby forming the complete active site. Our results provide novel structural insights into the role of PLP in terms of active site formation.